Implementation of Circular Economy as a Sustainable Development Strategy (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Sustainable development requires the implementation of innovations and radical changes to the concept of functioning of most countries, with particular emphasis on achieving environmental sustainability. The environment is not only the surroundings in which people live but also the resource base and place where economic activities are carried out. To ensure environmental sustainability, it is necessary to reduce the consumption of renewable resources, find alternatives to non-renewable resources and reduce waste generation and ecosystem pollution. To achieve integration between sustainability and economic development, the concept of a circular economy emerged as one of the basic concepts of the United Nations' 2030 Agenda for Sustainable Development. A circular economy is a new approach to dealing with global problems, with a particular focus on reducing resource consumption, reuse and recycling. Bearing in mind the importance of the concept of the circular economy, this paper aims to define the circular economy, to analyse the said concept with special reference to environmental sustainability, and to make a comparative analysis of the circular economy development in the European Union countries based on circular economy indicators. The results of the analysis indicate that there has been an improvement in circular economy indicators in all areas (production and consumption, waste management, secondary raw materials and competitiveness and innovation) in the analysed period.